Pengaruh Pengunaan Katalis Terhadap Laju Dan Efisiensi Pembentukan Hidrogen - Purnami, Purnami; Wardana, ING.; K, Veronika (Rekayasa Mesin, 2015)
Hydrogen was produced by steam reforming of kapok seed oil. CuZn as catalyst helps accelerate separation and increase production of hydrogen gas. This catalyst is viable and has high stability. Hydrogen gas was produced through 3 steps of catalyzing by mixed kapok seed oil and water with ratio of 1:1, 1:3 and 3:1. Heating temperature of catalyst at 250 C was selected. The rate and efficiency in forming of hydrogen gas were evaluated. From present investigation show that the more steps of catalyzing resulted in higher products, production rate, and efficiency in forming of hydrogen gas. Using 3 steps of catalyzing has promoted higher products, production rate, and efficiency in forming of hydrogen gas compared to 1 step and 2 step of catalyzing.